IMPLEMENTING E-PLANNING SYSTEM IN LOCAL GOVERNMENT DECISION-MAKING: A CASE STUDY IN INDONESIA - Rahayu, Nurul Widyawati; Supena, Stevy Hanny; Nurhayati, Siti; Irawan, Bambang; Hidayat, Hidayat (CosmoGov: Jurnal Ilmu Pemerintahan, 2023)
This study aims to evaluate the application of the e-planning system in local government decision-making in Indonesia. The research method used is descriptive with a qualitative approach. The study results show that the e-planning system in Indonesia has been implemented by several sectors, such as government, health, and education, through SIPPD, SIKDA, and PDSPK. Applying the e-planning system in local government decision-making has advantages such as efficiency, effectiveness, and planning, providing transparent information, increasing accountability, facilitating reporting and evaluation, human resources, budget constraints, and unsupportive policies. This research produces recommendations for increasing the implementation of the e-planning system in local government decision-making in Indonesia, such as increasing community participation, training, and education for system users, as well as stronger policy support. In conclusion, implementing an e-planning system can benefit local government decision-making, but it also requires efforts to overcome existing obstacles. This research is expected to contribute to the development of e-planning in Indonesia.gb777